Implementasi Kebijakan Retribusi Pelayanan Pasar Kembangsari berdasarkan Peraturan Daerah Kabupaten Semarang Nomor 8 Tahun 2011 (Telaah Pasal 61) - Perdana, Bintang Nusa; Rengga, Aloysius (Journal of Public Policy and Management Review, 2017)
The retribution of Market Services is a retribution charge as payment for the provision of traditional market facilities, such as the courts, stalls, kiosks, managed by the Regional Government, and specifically reserved for traders.Kembangsari market which is a first-class market in Semarang regency is a market that has achieved the lowest market retribution target in the last five years. The purpose of this study is to describe how the implementation of kembangsari market retribution policy based on Perda Kabupaten Semarang Nomor 8 Tahun 2011 and to identify supporting factors and resisting factors of the implementation of kembangsari market retribution policy based on Perda Kabupaten Semarang Nomor 8 Tahun 2011. This research is a descriptive study using a qualitative approach. The results showed that in the process of implementation of market service retribution policy based on Perda Kabupaten Semarang Nomor 8 Tahun 2011 there are phenomenon that considered not good enough such as accuracy of the policy, the accuracy of the implementor, accuracy in targeting,the accuracy of the process and accuracy of the process environment. In this study also found that supporting factors of the kembangsari market retribution policy is disposition and bureaucratic structure, whereas the resisting factors founded in communication factor and resources. Recommendation that can be given is to solve the problem concerning the ownership status of the market with attention to the clarity of the ownership letter, the certainty of government cooperation documents and administrative completeness in the process of buying and selling kiosks and los in kembangsari market.Adjustment of retribution targets with market environment conditions, increased intensity of socialization and addition of competent retribution staffing resources.